Family planning practice and its associated factors among women in Hulu Langat district, Selangor - M Jamsiah; MA Rahmah; WP Sh Ezat; AS Shamsul (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2009)
Background : Family planning is a method to control family size and to increase the intervals between chidbirths using multiple methods of contraceptives. Objectives : This study aims to determine the pravelance of family planning practice among married women (wife less than 55 years old) and its related factors and also to determine the husbands knowledge on family planning and their support. Methodology : This is a cross sectional study done through direct interviews amongst 118 married couples in Kampung Sesapan Batu Mingkabau, Hulu Langat Selangor. Results : On family planning practise, 43.2% of couples is currently practising, 22.0% have practiced but stopped and 34.8% have never used any types of family planning methods. As high as 75% of wives received support from their husband to pratice family planning. There is a significant association between family planning practice and wife’s age, husband’s age, wife’s occupation, wife’s education, wife’s knowledge and husband’s support. Husband’s knowledge , number of live children and husband’s education have no significant assocation in influencing family planning practice. Conclusion : To achieve better knowledge and family planning practises, husband’s involvement and support must be encouraged to ensure the correct informations and support are delivered to both couples. Approach through husbands is regarded as one of the key factors to the success of rural women family planning practice.